Logistyczna sprawność produktu – projektowanie wspomagające logistykę - Bielecki, Maciej M. (Wydawnictwo Politechniki Łódzkiej, 2018)
This monograph considers the subject of design for logistics and its outcome in the form of a logistically efficient product. It is a comprehensive study which not only provides an analysis of selected theoretical problems but also discusses research methods and methodologies in the field [...]. The monograph is intended as the first step in research on identification of conditions underlying design for logistics and characterization of the concept logistic efficiency of products. One should hope that in spite of the many boundary conditions and constraints discussed herein, the introduced model of logistic efficiency of products will contribute to the strengthening of the competitiveness of manufacturing companies by demonstrating to designers the extent to which their work impacts on the effectiveness and efficiency of logistic processes down the line. The monograph also does the groundwork for the transformation of production processes for the fourth industrial revolution - Industry 4.0, where product design that considers technology, assembly, quality, and logistics will play a critical role.
Projekt okładki : Grochowska, Daria
Keywords: logistic product efficiency; design supporting logistics; logistic processes; Industry 4.0; logistyczna sprawność produktu; projektowanie wyrobu; Przemysł 4.0 (czwarta rewolucja przemysłowa); inżynieria produkcji